Factors associated with the publication and impact of CUA abstracts over the last decade - Al-Daqqaq, Zizo; Rajesh, Zwetlana; Ahmad, Ihtisham; Khosh Kish, Ealia; Abed, Haider; Welk, Blayne (Canadian Urological Association Journal, 2024)
INTRODUCTION: The Canadian Urological Association’s (CUA) annual meeting is the largest gathering of Canadian urologists, and many abstracts that are presented go on to be published as peer-reviewed papers. Our objective was to determine the publication rates and impact of these abstracts, and examine predictors associated with their publication. METHODS: We identified abstracts presented at the 2010, 2013, 2014, 2015, 2018, 2020, and 2021 CUA meetings, and determined if there were matching manuscripts based on author and title using a comprehensive Medline search. Standardized data was extracted. Medians and interquartile ranges are presented, and regression models were used to determine factors associated with manuscript publication, journal impact factor, and time to publication. RESULTS: There were 1732 CUA abstracts in our years of interest. The overall publication rate was 45.4%. Median journal impact factor was 2.27 for all published abstracts and time to publication was 13.2 months. Type of presentation was significantly associated with publication rate (p<0.001), with 63.7% of podiums, 46.7% of moderated posters, and 39.5% of unmoderated posters published. The median journal impact factor was 3.45 for published podiums, 2.19 for moderated posters, and 2.10 for unmoderated posters. CONCLUSIONS: Approximately 45% of CUA annual meeting abstracts are eventually published. The type of presentation correlates well with both publication and impact factor, suggesting the CUA review process and scientific program committee does a good job of judging abstract quality.